In vitro studies of the neuroprotective activities of astaxanthin and fucoxanthin against amyloid beta (Aβ1-42) toxicity and aggregation. (March 2019) - Alghazwi, Mousa; Smid, Scott; Musgrave, Ian; Zhang, Wei
Abstract: Amyloid beta (Aβ) can aggregate and form plaques, which are considered as one of the major hallmarks of Alzheimer's disease. This study aims to directly compare the neuroprotective activities in vitro of two marine-derived carotenoids astaxanthin and fucoxanthin that have shown a spectrum of biological activities, including neuroprotection. The in vitro neuroprotective activities were investigated against Aβ1-42 -mediated toxicity in pheochromocytoma (PC-12) neuronal cells using the MTT cell viability assay, anti-apoptotic, antioxidant and neurite outgrowth activities; as well as inhibition against Aβ1-42 fibrillization in the Thioflavin T (ThT) assay of fibril kinetics and via transmission electron microscopic (TEM) evaluation of fibril morphology. The results demonstrated that both astaxanthin and fucoxanthin exhibited multi-neuroprotective effects favouring fucoxanthin over astaxanthin supporting neuroprotective roles of marine-derived carotenoids as potential novel dementia prevention or therapeutic strategies. Highlights: Astaxanthin and fucoxanthin provided neuroprotection against Aβ1-42 . Both compounds showed anti-aggregation effects against Aβ1-42 . Both compounds demonstrated multiple neuroprotective activities. Fucoxanthin showed higher anti-aggregation and neurite outgrowth activity.